2018
DOI: 10.1103/physrevd.97.114015
|View full text |Cite
|
Sign up to set email alerts
|

Double Collins effect in e+eΛΛ¯

Abstract: We study the Collins function H ⊥ 1 of the Λ hyperon, which describes the fragmentation of a transversely polarized quark into an unpolarized Λ hyperon. We calculate H ⊥ 1 for light quarks of the Λ hyperon, in the diquark spectator model with a Gaussian form factor for the hyperon-quarkdiquark vertex. The model calculation includes contributions from both the scalar diquark and vector diquark spectators. Using the model result, we estimate the azimuthal asymmetry A 12 , which appears in the ratio of unlike-sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 117 publications
(151 reference statements)
0
3
0
Order By: Relevance
“…a calculation in a diquark spectator model resulted in sizable Collins functions for up and down quarks into Λ hyperons [145]. While no such calculation is presented for the case of protons, it is not unplausible that it would result in a non-vanishing Collins effect, as hinted at by the data.…”
Section: Jhep12(2020)010mentioning
confidence: 91%
“…a calculation in a diquark spectator model resulted in sizable Collins functions for up and down quarks into Λ hyperons [145]. While no such calculation is presented for the case of protons, it is not unplausible that it would result in a non-vanishing Collins effect, as hinted at by the data.…”
Section: Jhep12(2020)010mentioning
confidence: 91%
“…This approach can be applied to quark propagation in cold nuclei and hadron suppression in semiinclusive deeply inelastic scattering (SIDIS) off large nuclei [26,27] as well as hadron suppression due to jet propagation in QGP in heavy-ion collisions [28,29]. In the most recent study of multiple parton scattering in SIDIS off large nuclei and Drell-Yan dilepton production in p + A collisions at NLO within the higher-twist framework [30,31,32], the factorization is verified for the transversemomentum weighted cross section. The QCD evolution equation for twist-4 matrix elements for parton correlation or the jet transport coefficient, is also derived and its universality is demonstrated.…”
Section: Parton Energy Lossmentioning
confidence: 99%
“…The authors have suggested that the attack at the carbon or sulphur centres depends on the reagent used, and the yield of S N Ar or S N products is strongly influenced by the solvent. Currently, solvent effect in S N Ar reactions has been studied in conventional organic solvents (COS) 10,12,[19][20][21][22][23][24] and room temperature ionic liquids (RTILs); 12,17,18,20,[25][26][27][28] this opens the discussion of the factors that determine selectivities, reaction rates, and mechanisms. For instance, D'anna et al 18 investigated the reaction of 2-substituted 5-nitrothiophenes with secondary amines.…”
Section: Introductionmentioning
confidence: 99%